Evolutionary trends in the columnar cactus genus Eulychnia (Cactaceae) based on molecular phylogenetics, morphology, distribution, and habitat. Issue 7 (3rd October 2018) - Larridon, Isabel; Walter, Helmut E.; Rosas, Marcelo; Vandomme, Viki; Guerrero, Pablo C.
Abstract : Populations of the columnar cactus genus Eulychnia (Cactaceae) are an iconic sight in the Chilean Atacama Desert. The most recent taxonomic treatment of the genus suggested to accept up to seven taxa at species level based on morphological data. To date, species boundaries and infrageneric relationships in Eulychnia have not been investigated using a molecular approach. In this study, sequence data were generated for six chloroplast markers ( rpl32-trnL, trnH-psbA, trnL-trnF, trnQ-rps16, trnS-trnG, and ycf1 ) for the seven species. Where possible, samples were collected from the south and north of the distribution range of widely distributed species, as well as plants from two morphologically distinct populations in the Atacama and Coquimbo Regions. Evolutionary trends of morphological characters were investigated using ancestral state reconstruction, and the habitat of the Chilean taxa was taken into account based on latitudinal and altitudinal distribution, precipitation regime, and vegetation zones. Two major clades were retrieved in the molecular phylogenetic hypotheses, a northern clade and a southern clade, which can easily be distinguished morphologically by differences in rib shape and type of the indumentum of the pericarpel and the hypanthium. The only Eulychnia taxon found outside Chile is most commonly accepted as Eulychnia iquiquensis subsp. ritteri . However, its isolated geographic distribution and the fact that this taxon is not most closely related to E. iquiquensis but was retrieved as sister to the rest of the northern clade in our molecular phylogenetic results support the recognition of E. ritteri at species level. Our results also provide some support for the two recently published species, E. chorosensis (previously placed in E. acida s.l.) and E. taltalensis (previously considered to be part of E. breviflora s.l.). The relationships in the southern clade need further study.